Solid Fuels and Heavy Hydrocarbon Liquids : Thermal Characterization and Analysis /: Thermal Characterization and Analysis. (2017) - Kandiyoti, Rafael; Herod, Alan; Bartle, Keith D; Morgan, Trevor J
No abstract available